Nauportus- an Early Roman trading post at Dolge njive in Vrhnika: The results of geophysical prospecting using a variety of independent methods - Mušič, Branko; Horvat, Jana (Arheološki vestnik, 2007)
The Early Roman trading post at Dolge njive formed a part of Nauportus - a vicus on the town territory of Aquileia. The site was investigated using various geophysical methods: geoelectric resistivity, electrical conductivity, magnetometry, and Ground Penetrating Radar (GPR). The results are presented in view of the complementarity of these methods. The data from earlier archaeological excavations were used to plan an appropriate and effective research strategy. The results from geophysical prospecting were combined with the ground plans resulting from former excavations and a new ground plan of the trading post was engendered. A 3D portrayal of the architectural remains was enabled by georadar sounding. The site was fortified with a defence wall and towers as well as a defence ditch. One third of the interior surface was covered by the market place, which was surrounded by storehouses (horrea) with a portico and tabernae. An ambulatory type temple was also found here. Similar architecture is known primarily from Republican set-tlements in Italy and from Roman ports. The chronology of the small finds was reviewed and the results place the origins of the site in the Pre-Augustan or Early Augustan periods, and its decline in the 1st century AD.